2006
DOI: 10.1093/aob/mcl154
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation by White Lupin under Phosphorus Deficiency

Abstract: Enhanced nodulation in cluster root zones and increased potential for organic acid production in root nodules appear to contribute to white lupin's resilience to P-deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
131
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 50 publications
10
131
0
2
Order By: Relevance
“…No visible anthocyanin accumulated in PdL, nor did we observe any other differences in the growth of P i -sufficient and P i -deficient aerial tissues. These results are consistent with previous studies, which showed that P i -sufficient and P i -deficient plants at 25 DAE exhibit differences in P i concentrations but show no change in overall growth responses (Schulze et al, 2006). Our analyses comparing P i -sufficient and P i -deficient transcript expression patterns at 16 DAE provide insight into gene expression profiles as plants experience P i deficiency.…”
supporting
confidence: 92%
“…No visible anthocyanin accumulated in PdL, nor did we observe any other differences in the growth of P i -sufficient and P i -deficient aerial tissues. These results are consistent with previous studies, which showed that P i -sufficient and P i -deficient plants at 25 DAE exhibit differences in P i concentrations but show no change in overall growth responses (Schulze et al, 2006). Our analyses comparing P i -sufficient and P i -deficient transcript expression patterns at 16 DAE provide insight into gene expression profiles as plants experience P i deficiency.…”
supporting
confidence: 92%
“…Most studies on the effect of P limitation on N 2 -fixation have largely been confined to model legumes such as Lupinus albus (Schulze et al, 2006, Thuynsma et al, 2013 and Medicago truncatula (Tang et al, 2001, Sulieman et al, 2013. Despite the high legume diversity found on the P-poor soils of the CFR (Goldblatt and Manning 2002), little is known about the functional mechanisms which affect N nutrition within the nodules of indigenous legumes.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen fixing systems require more phosphorus (P) than non-N 2 fixing systems, because the process consumes large amounts of energy, and energy-generating metabolism strongly depends upon the availability of P (Schulze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%